Control of Sulfide Production in High Salinity Bakken Shale Oil Reservoirs by Halophilic Bacteria Reducing Nitrate to Nitrite - An, Biwen A.; Shen, Yin; Voordouw, Gerrit (Frontiers in Microbiology, 2017)
Microbial communities in shale oil fields are still poorly known. We obtained samples of injection, produced and facility waters from a Bakken shale oil field in Saskatchewan, Canada with a resident temperature of 60°C. The injection water had a lower salinity (0.7 Meq of NaCl) than produced or facility waters (0.6-3.6 Meq of NaCl). Salinities of the latter decreased with time, likely due to injection of low salinity water, which had 15-30 mM sulfate. Batch cultures of field samples showed sulfate-reducing and nitrate-reducing bacteria activities at different salinities (0, 0.5, 0.75, 1.0, 1.5 and 2.5 M NaCl). Notably, at high salinity nitrite accumulated, which was not observed at low salinity, indicating potential for nitrate-mediated souring control at high salinity. Continuous culture chemostats were established in media with volatile fatty acids (a mixture of acetate, propionate and butyrate) or lactate as electron donor and nitrate or sulfate as electron acceptor at 0.5 to 2.5 M NaCl. Microbial community analyses of these cultures indicated high proportions of Halanaerobium, Desulfovermiculus, Halomonas and Marinobacter in cultures at 2.5 M NaCl, whereas Desulfovibrio, Geoalkalibacter and Dethiosulfatibacter were dominant at 0.5 M NaCl. Use of bioreactors to study the effect of nitrate injection on sulfate reduction showed that accumulation of nitrite inhibited SRB activity at 2.5 M but not at 0.5 M NaCl. High proportions of Halanaerobium and Desulfovermiculus were found at 2.5 M NaCl in the absence of nitrate, whereas high proportions of Halomonas and no SRB were found in the presence of nitrate. A diverse microbial community dominated by the SRB Desulfovibrio was observed at 0.5 M NaCl both in the presence and absence of nitrate. Our results suggest that nitrate injection can prevent souring provided that the salinity is maintained at a high level. Thus, reinjection of high salinity produced water amended with nitrate maybe be a cost effective method for souring control.